Application of response surface methodology on photocatalytic degradation of Astrazon Orange G dye by ZnO photocatalyst: Internal mass transfer effects - Murshed, Mohammed Khisro; Dursun, Arzu Yadigar; Dursun, Gulbeyi (Elsevier, 2022)
The present study involves the removal of Astrazon Orange G dye from aqueous solutions by ZnO in a heterogeneous system of using UV-C light as a source of energy. Crystalline structure and BET surface area of the photocatalyst were characterized. The optimum conditions were determined as 200 mg dm(-3) of dye concentration, 4 g dm(-3) of catalyst amount, pH of 6, the temperature of 40 degrees C, and 0.2 dm(3) min(-1) of the rate of airflow. Under these conditions, the dye and TOC removal efficiencies at 75 min were determined as 97.9 % and 54.7 %, respectively. Response surface methodology was also used to investigate the interactive effects of the selected parameters and the optimum conditions for maximum degradation of AOG dye. The kinetics of the Astrazon Orange G dye photodegradation by using ZnO represented by the first-order equation. The effect of the temperature on the AOG dye photodegradation was shown by using of the Arrhenius equation. The activation energy was found to be 4.28 kJ mol(-1). In addition, internal mass transfer effects on photo-degradation of AOG dye were investigated with different sizes ZnO and effectiveness factors, Thiele modulus, and average effective diffusion coefficient were calculated. These results showed that the intraparticle mass transfer did not have much effect on the reaction rate and the chemical step largely controlled the rate. The potential performance of these photocatalytic processes on the synthetic wastewater was also tested. (c) 2022 Published by Elsevier Ltd on behalf of Institution of Chemical Engineers.
Keywords: Photocatalysis; Astrazon Orange G dye; Response surface methodology; Kinetics; Intraparticle diffusion effects